2021
DOI: 10.4274/tjh.galenos.2021.2020.0717
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the HEAD-US Scoring System for Observing the Protective Effect of Prophylaxis in Hemophilia Patients: A Prospective, Multicenter, Observational Study

Abstract: Objective: This study aimed to observe the preventive effect of prophylactic treatment on joint health in people with hemophilia (PwH) and to investigate the importance of integration of ultrasonographic examination into clinical and radiological evaluation of the joints. Materials and Methods: This national, multicenter, prospective, observational study included male patients aged ≥6 years with the diagnosis of moderate or severe hemophilia A or B from 8 centers across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The reasons for excluding studies based on full text are summarized in Supplement S2. Eventually, 15 studies 11,12,15,24,29,[38][39][40][41][42][43][44][45][46][47] were included in the systematic review. The 15 included studies reported on occurrence of swelling and synovial proliferation in 2890 joints of 627 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for excluding studies based on full text are summarized in Supplement S2. Eventually, 15 studies 11,12,15,24,29,[38][39][40][41][42][43][44][45][46][47] were included in the systematic review. The 15 included studies reported on occurrence of swelling and synovial proliferation in 2890 joints of 627 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven out of 15 included studies were considered 'screening of index joints' studies 24,29,[38][39][40][41][43][44][45][46][47] and were thus included in a bivariate random-effects model to determine summary estimates for sensitivity and specificity. Subclinical synovial proliferation was found in 4.6-41.7% of the joints in these studies.…”
Section: Meta-analysis Of Screening Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Studies in the literature have shown a correlation between HJHS, a clinical assessment scale, and HEAD-US. [22][23][24] It is seen that articular symptoms in subclinical cases can be detected earlier by HEAD-US.…”
Section: Discussionmentioning
confidence: 99%
“…However, as well as there being difficulties in using MRI with children, it is expensive and there is limited availability in resource-constrained settings. Ultrasound is effective in assessing changes to soft tissue and cartilage in early arthropathy [16,17] and its use with the HEAD-US scoring system has shown similar sensitivity [19] . X-rays are not sensitive enough to detect early arthropathy but can show changes in the later stages when arthropathy is already established.…”
mentioning
confidence: 99%